Technology facilitated best practices in digital preservation management: the experience of Kenneth Dike Library, University of Ibadan, Nigeria (2019)
Digital preservation is a global phenomenon and current trend that guarantees the maintenance of information contents. Libraries should he particularly concerned with digital preservation because digital resources of different types are increasingly becoming parts of their collections and as such need to be preserved for wider visibility access and posterity Kenneth Diki Library (KDL), University of Ibadan, Nigeria over the rears luis developed sets of best practices that have made digital preservation a success. Therefore, this paper discusses the facilities and processes put in place in KDL that ensure effective management of digital information contents that other universities could learn from in addition, the paper also highlights the challenges of digital preservation that are peculiar to the Nigerian environment. The paper suggests that funding digital preservation project should be given the topmost priority other suggestions include: acquisition of modern digital preservation equipment, employment of more staff, development of staff expert is; and exploration of other sources of electricity supply.